The extractives industry: (un)likely and (un)welcome partners in regenerating Indigenous cultures in Canada?. Issue 1 (1st January 2021) - van Luijk, Nicolien; Giles, Audrey; Millington, Rob; Hayhurst, Lyndsay
ABSTRACT: In this paper, we critically examine the ways in which the extractives industry in Canada is engaging in partnerships with Indigenous-led organizations that promote Indigenous cultural practices through leisure and cultural programmes. We examined two cases in Canada, the Northwest Territories On The Land Collaborative that partners with Dominion Diamond and Diavik Diamond Mines, and the Urban Native Youth Association, an organization that is partnering with Suncor Energy Inc. to develop a Native Youth Centre in Vancouver, British Columbia. Our findings reveal that these extractives companies are being framed as positive partners for the regeneration of Indigenous cultures in Canada, while at the same time continuing to have negative environmental and social impacts on Indigenous communities. These findings build on a growing critical consensus that corporate social responsibility practices are part of a strategy that allows corporations to gain legitimacy and access to resources whilst protecting their economic bottom line.